"Lecciones aprendidas de la crisis de finales de los noventa aplicadas a la industria de la construcción" (2017)
This paper will focus on documenting the Lessons Learned during the Crisis of the Construction Industry of the late twentieth century, how the 1990s was a turning point in the management of construction projects and how each of the participants in The industry had to modify many of its habitual practices to be able to adapt to the new form of business.